Effect of Submerged Arc Welding (SAW) Slag Waste on CBR Value of Subgrade - Fajar Ilham; Yelvi (Politeknik Negeri Jakarta, 2025)
This research aims to identify the effect of the addition of SAW (Submerged Arc Welding) slag waste on the value of California Bearing Ratio (CBR) on clay soil. This research was conducted at the Civil Engineering Laboratory, Politeknik Negeri Jakarta, with an experimental method using a variation of SAW waste mixture of 0%, 5%, 10%, 15%, and 20%. Laboratory tests include specific gravity, grain size analysis, Atterberg limit, compaction, and CBR tests in accordance with SNI standards. The results showed that the addition of SAW waste increased the specific gravity of clay soil from 2.545 to 2.691. The value of liquid limit, plastic limit, and plasticity indexdecreased with the increase of SAW waste content. In compaction tests, the maximum dry density increased from 1.259 gr/cm³ to 1.335 gr/cm³ at 15% SAW waste, but decreased at 20% to 1.329 gr/cm³. The CBR value also showed an increase up to 15% SAW waste from 1.77% to 3.95%, but decreased at 20% to 2.83%. In conclusion, SAW slag waste can increase the bearing capacity of clay soil up to a certain level, but excessive addition reduces the CBR value.